A Representação Brasileira no Cinema de Animação Nacional, identidade, mercado cinematográfico e prática artística - Oliveira, Isabela Veiga (2013)
This study aims to reflect varied viewpoints on the concept of "identity" and its development throughout history, emphasizing the post-modernity, its relationship with the social imagination, mass culture and memory. We direct this study to the Brazilian culture and cinema as a support for the representation of Brazilian identity. To demonstrate this concept reflected in national production and look at the film market in full development from incentive laws, we analyzed three animated feature films: Brichos (2007), A Turma da Mônica em uma Aventura no Tempo (2007) and Brasil Animado (2011). Finally, from these studies and personal experiences, we held the poetic "A Velha Gulosa", a fiction film with animated inserts, financed through municipal incentive laws.